Disposition and metabolism of sulfolane in Harlan Sprague Dawley rats and B6C3F1/N mice and in vitro in hepatocytes from rats, mice, and humans. (2nd April 2020) - Waidyanatha, Suramya; Black, Sherry R.; Blystone, Chad R.; Patel, Purvi R.; Watson, Scott L.; Snyder, Rodney W.; Fennell, Timothy R.
Abstract: Sulfolane has been found as a ground water contaminant near refining sites. These studies investigated the in vitro hepatic clearance and in vivo disposition of [ 14 C]sulfolane in rats and mice following a single oral administration (30, 100, or 300 mg/kg) and dermal application (100 mg/kg). [ 14 C]Sulfolane was well-absorbed in male rats following oral administration and excreted extensively in urine (≥93%). Total radioactivity in tissues at 24 and 48 h was ∼7% and <2%. Disposition pattern was similar in female rats and male and female mice at 100 mg/kg oral dose. Dermally applied [ 14 C]Sulfolane (covered dose site, 100 mg/kg) was poorly absorbed in male (∼16%) and female (∼19%) rats; absorption increased to 59% when the dose site was uncovered in male rats suggesting ingestion of dose via grooming of the dose site. Dermally applied [ 14 C]sulfolane (100 mg/kg, covered dose site) was well absorbed in male (∼70%) and female (∼80%) mice. Urinary radiochemical profiles were similar between routes, species, and sexes; the main analytes present in urine were sulfolane and 3-hydroxysulfolane. Sulfolane was not cleared in hepatocytes from rodents or human suggesting sites other than liver might be involved in metabolism of sulfolane in vivo .